Horizontal and Vertical Migration of Anglerfish Lophius piscatorius in Relation to Hydrography in Faroese Waters - Ofstad, Lise Helen; Hátún, Hjálmar; Pedersen, Torstein; Steingrund, Petur; Mikkelsen, Bjarni (Frontiers in Marine Science, 2022)
Adult anglerfish conduct annual migrations between spawning areas and feeding areas; for Faroese waters this migration has so far not been described. Therefore, anglerfish migration and distribution in Faroese waters was investigated by mark-recapture studies, including data storage tags, as well as data from scientific trawl surveys, commercial trawlers and gillnetters. The fish distribution was compared to hydrographical conditions such as sea surface- and bottom temperature. A clear seasonal offshore-onshore migration was observed. Anglerfish occupied shallower waters (<200 m) during summer and deeper waters, especially on the western side of the Faroe shelf, during winter. This seasonal movement was most evident for sexually mature fish longer than 70 cm indicating spawning in deep waters during winter. Further, during winter anglerfish experienced cold water, which indicated that they were distributed close to the main interface of cold water masses surrounding the shelf. The fish were mostly located in warm water (6.5–11°C) and seldom occurred in colder waters than 4°C. Anglerfish appeared generally inactive, only around 5% of the total data storage tag recordings showed more than 5 m vertical movement between two subsequent hourly recordings. This vertical activity varied seasonally by being higher during winter than summer and diurnally by being higher during night time than day time, indicating that sunrise and day length played an important role in vertical movements.